2019
DOI: 10.1111/zph.12570
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of swimmer's itch in Central Italy: Description, causative agent and preventive measures

Abstract: Swimmer's itch is caused by the penetration of free-swimming larvae of trematodes of the family Schistosomatidae in human skin. It is usually reported in people engaged in recreational water activities in freshwater bodies and in most of cases, it is provoked by bird schistosomes of the genus Trichobilharzia. In the summer 2017, many cases of dermatitis were recorded in people bathing in the waters of the Albano Lake (Rome, Italy) and a parasitological investigation was carried out in order to ascertain the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The first three species have been previously reported from several countries in Europe, including Denmark (Horák et al, 2009(Horák et al, , 2015Cichy et al, 2011;Soldánová et al, 2013;Christiansen et al, 2016;De Liberato et al, 2019). However, this is the first report on the identification of T. anseri from Danish lakes, which links this work to a few previous findings in Europe (Jouet et al, 2015).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The first three species have been previously reported from several countries in Europe, including Denmark (Horák et al, 2009(Horák et al, , 2015Cichy et al, 2011;Soldánová et al, 2013;Christiansen et al, 2016;De Liberato et al, 2019). However, this is the first report on the identification of T. anseri from Danish lakes, which links this work to a few previous findings in Europe (Jouet et al, 2015).…”
Section: Discussionsupporting
confidence: 59%
“…anseri . The first three species have been previously reported from several countries in Europe, including Denmark (Horák et al ., 2009, 2015; Cichy et al ., 2011; Soldánová et al ., 2013; Christiansen et al ., 2016; De Liberato et al ., 2019). However, this is the first report on the identification of T .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, cercarial dermatitis (or swimmer's itch) represents a neglected allergic condition which develops after repeated exposure to avian schistosomes [30,31]. Being regarded as an emerging disease, cercarial dermatitis has substantial health and economic consequences, especially if outbreaks afflict recreational bathing areas [32][33][34][35].…”
mentioning
confidence: 99%
“…Various studies stated that disorders related to the digestion system are the most common disease in a public bath. The results showed that the epidemic of cercarial dermatitis occurred due to Trichobilharzia franki in snails as an intermediate host (39). The longer the contact with the water, the higher the risk of getting infected by pathogens in the water.…”
Section: Health Complaints To Eyes Ears and Skinmentioning
confidence: 98%
“…Visitors who swim will likely have a higher risk of getting infected by diseases than those who do not. A study suggested that the diseases were not only related to digestion but also respiratory (39). Other studies suggested that respiratory disease experienced by visitors of public baths may come from the presence of Adenovirus droplets in the water (11).…”
Section: Health Problems Of Public Bath Visitorsmentioning
confidence: 99%